A parametric study of DMS subjected to induced low-stress consolidation and heat treatment - Chong, Wen Jing; Chan, Chee Ming; Tuan Ismail, Tuan Noor Hasanah (Penerbit UTHM, 2020)
Dredging activities are important either in the control the accessibility and navigability to harbours or the maintenance to the existing facilities. Dredged marine sediments (DMS) is the products generated from dredging activities. DMS consists mainly of clays, silts and sand mingled with rocks, debris, larger obstacles and organic matter such as polycyclic aromatic hydrocarbons (PAHs) and polychlorinated aromatic biphenyl (PCBs)